Promising activity against NTERA-2 cancer stem cells of malloapelta B compound isolated from the Bum-bup plant in Vietnam - Thao, Do Thi; Nga, Nguyen Thi; Cuc, Nguyen Thi; Phuong, Do Thi; Ha Phuong, Trieu; Hai Yen, Pham Thi; Tuan Anh, Hoang Le (Vietnam Journal of Biotechnology, 2020)
Recent studies have revealed that cancer stem cells (CSCs) drive tumor growth, metastasis, therapy resistant and recurrence. Therefore, CSCs are considered as new targets for screening of more effective drugs. The compound malloapelta B, which was isolated from the Bum-bup plant (Mallotus apelta) (Lour.) Muel.-Arg, Euphorbiaceae) in Vietnam, presented very potent and strong anticancer invitro, especially against the activation ofNF-kB (nuclear factor- kappa B). In our research, malloapelta B inhibited the growth of NTERA-2 line, a CSC line, at the value of IC50 = 12.71 ± 0.76 µM. In this study, malloapelta B also had effects on cell cycle of NTERA-2 by significantly reducing the cell number at G0/G1 phase (37.48%), while raising this number of phase G2/M to 31.12% in comparison with those of control (56.81% and 18.6%, respectively). Besides, clonogenic and tumorspheroidal formations are acknowledged as typically renewable characteristics of CSCs. Then, in our studies, malloapelta B significantly prevented NTERA-2 to form clonogens and reduced tumorspheres’ sizes at treatments with 20 and 100 µg/mL. However, malloapelta B did not exhibit any obvious effects on the expression level of CD44+/CD24+, the two typical cell surface markers of CSCs, at 2.5 and 5 µM treatments.